Kemampuan Siswa Kelas X SMA Negeri 2 Banda Aceh Mengembangkan Isi Teks Eksposisi Melalui Model Group Investigation - Nuramalina Harvianti; Yusri Yusuf; Muhammad Idham (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is about the ability of class X students of SMA Negeri 2 Banda Aceh in developing the contents of the exposition text through Model Group Investigation. in this study, the problems raised by researchers were, (1) how the students 'ability to identify the main ideas in the exposition text, (2) how the students' ability to identify explanatory ideas in the exposition text. The population in this study were all grade X students of SMA Negeri 2 Banda Aceh, totaling 258 students. Semple is taken at intervals. In this study, researchers used quantitative descriptive methods. The process of collecting data uses test techniques. After that, the data that has been obtained, is processed using quantitative techniques in the form of average calculations. The average value obtained from the data analysis shows that the ability of class X students of SMA Negeri 2 Banda Aceh identifies each aspect, the average value obtained by students from aspects identifying the main ideas in the exposition text is 86.22, the value is classified into in the very good category. The average value obtained by students from the aspect of identifying explanatory ideas in the exposition text is 83.06, the value is classified into either category. The average value of all aspects obtained by grade X students of SMA Terror 2 Banda Aceh is 79.42, the value is classified into a good category that is in the range of 70-84 grades